Deficit financing and economic development : with special reference to Indian economic development - Kulkarni, R. G. (Bombay : New York : Asia Pub. House, 1966)
The book examines deficit financing with particular reference to India second five year plan and third year draft plan.
"Originally submitted with some differences in the matter to the University of Poona as a doctoral thesis."
Includes bibliographical references: p. 391-395.
usc 23/01/2019
Loans
Keywords: Deficit financing; Economic policy; Economic history; India